Utilizing Canva for Designing Effective Flashcards in Vocabulary Instruction for Young Learners: A Descriptive Qualitative Study - Fitria, Tira Nur; Afdaleni, Afdaleni; Simbolon, Nurmala Elmin (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2024)
This research describes the creation of flashcard media in teaching vocabulary to young learners. This research is descriptive qualitative. This research involved collecting data from the Canva website, primarily through direct observation of the various features, tools, and processes involved in creating flashcards. Data analysis was carried out by comparing the various features and tools available in Canva ofmaking flashcards, as well as identifying the ease of use and advantages of the application in the process of making flashcards. The analysis shows that English for Young Learners (EYL) is a program designed to teach basic vocabulary and simple language structures to children. Flashcards are highlighted as an effective tool in this process, as they help children associate words with real objects, improve understanding, and enhance vocabulary retention. Selecting the right vocabulary is crucial for building confidence, improving communication skills, and supporting reading and listening development. Flashcards are adaptable, providing engaging activities that reinforce word meanings and language concepts. Canva is recommended for creating customizable and engaging flashcards. Effective flashcards should include relevant words or phrases, clear definitions or translations, example sentences, and appropriate images or illustrations. The design should be clear, with large, easy-to-read letters, and a consistent format for each word. Regular review and a focus on design, visualization, and interactive activities can further enhance the learning experience. Engaging students in collaborative and evaluative activities also strengthens their understanding. Overall, by following these strategies, flashcards can be a powerful tool in introducing and reinforcing English vocabulary for young learners, with Canva serving as a valuable resource for creating effective learning materials.